Deploying Video Analysis to Boost Instruction and Assessment in Physical Education - Laughlin, Michael K.; Hodges, Michael; Iraggi, Taylor (Journal of Physical Education, Recreation & Dance, 2019)
Physical educators are discovering the benefits of using video analysis to support their instruction and assessment. Slow-motion playback, zoom, and voice-over narration are just some of the features built into increasingly affordable mobile devices and applications that can easily be used by teachers to support student learning. Additionally, with the use of video technology, teachers are finding creative ways to provide instant motor-performance feedback which can be easily documented for assessment purposes. Yet, with any novel technology tool, internal and external challenges exist that may prevent teachers from realizing the myriad of benefits. This article provides a background on mobile video analysis tools, along with strategies to help physical educators discover ways to effectively implement this engaging technology into their curriculum.
7 citations (Crossref) [2023-10-31] _eprint: https://doi.org/10.1080/07303084.2019.1580637
Keywords: dept.hms; peer-reviewed

Effects of an adapted physical education training package on special education teacher instruction - Laughlin, Michael K.; Murata, Nathan M.; McDougall, Dennis (Behavioral Interventions, 2019)
This study investigated the impact of an adapted physical education training package on functional motor skill instruction of three special education teachers who instructed secondary students with low-incidence disabilities. The training package emphasized teachers' use of systematic prompting and specific reinforcement teaching strategies plus adapted physical education consultation. We used a multiple baseline design and collected data on the three teachers' use of systematic prompting and specific reinforcement plans during videotaped teaching trials. We also collected data on how teachers documented their instructional strategies, and we analyzed personal reflections that teachers wrote in the journals. Results indicated that with each of the three teachers, correctly implemented functional motor skill instructional performance improved after they completed the training package.
0 citations (Crossref) [2023-10-31] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/bin.1653
Keywords: dept.hms; functional motor skills; peer-reviewed; prompting; reinforcement; severe disabilities; special education